EF-modstanden 1972-1986. Bidrag til et stykke Danmarkshistorie. Festskrift til Poul Overgaard Nielsen. (Forlaget Hedeskov, 1986) 120 s., 145,00 kr. - Lehmann Sørensen, Carsten (Historie/Jyske Samlinger, 1989)
-